2008
DOI: 10.1007/s11590-008-0086-5
|View full text |Cite
|
Sign up to set email alerts
|

Modified nonlinear conjugate gradient methods with sufficient descent property for large-scale optimization problems

Abstract: It is well known that the sufficient descent condition is very important to the global convergence of the nonlinear conjugate gradient method. In this paper, some modified conjugate gradient methods which possess this property are presented. The global convergence of these proposed methods with the weak Wolfe-Powell (WWP) line search rule is established for nonconvex function under suitable conditions. Numerical results are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(66 citation statements)
references
References 17 publications
0
64
0
2
Order By: Relevance
“…Email: xrli68@163.com 收稿日期:2011 年 3 月 12 日;修回日期:2011 年 3 月 20 日;录用日期:2011 年 3 月 21 日 摘 要:Yuan [15] 提出了修改的 PRP 共轭梯度方法,该方法能保证参数 k [1,2], , [7], ( ) …”
Section: 李向荣 广西大学数学与信息科学学院,南宁unclassified
See 1 more Smart Citation
“…Email: xrli68@163.com 收稿日期:2011 年 3 月 12 日;修回日期:2011 年 3 月 20 日;录用日期:2011 年 3 月 21 日 摘 要:Yuan [15] 提出了修改的 PRP 共轭梯度方法,该方法能保证参数 k [1,2], , [7], ( ) …”
Section: 李向荣 广西大学数学与信息科学学院,南宁unclassified
“…
Abstract:Yuan [15] proposed a modified PRP conjugate gradient method which can ensure that the scalar 0  k  holds and the search direction possesses the sufficient descent property without any line search. This technique has been extended to other conjugate gradient methods, but the convergence has been not given.
…”
mentioning
confidence: 99%
“…The PRP algorithm [6,7] is one of the most effective CG algorithms and its convergence can be found (see [7,9,10], etc.). Powell [9] suggested that should not be less than zero; then many new CG formulas are proposed (see [11][12][13][14][15][16][17], etc.) to ensure the scalar ≥ 0.…”
Section: Introductionmentioning
confidence: 99%
“…This counter-example also indicates that the method has a drawback that it is impossible to be convergent when the objective function is nonconvex. Therefore, during the past few years, much effort has been investigated to create new formulae for b k , which not only possesses global convergence for general functions but also is superior to original method from the computation point of view (see [8][9][10][11][12][13][14][15][16][17]). …”
Section: Introductionmentioning
confidence: 99%